Chapter 3: Spatial point patterns: Models and statistics - Baddeley, Adrian (2013)
This chapter gives a brief introduction to spatial point processes, with a view to applications. The three sections focus on the construction of point process models, the simulation of point processes, and statistical inference. For further background, we recommend [Daley et al., Probability and its applications (New York). Springer, New York, 2003/2008; Diggle, Statistical analysis of spatial point patterns, 2nd edn. HodderArnold, London, 2003; Illian et al., Statistical analysis and modelling of spatial point patterns. Wiley, Chichester, 2008; Møller et al., Statistical inference and simulation for spatial point processes. Chapman & Hall, Boca Raton, 2004]. © Springer-Verlag Berlin Heidelberg 2013.